Performance and profitability of calves and yearlings in Southeast Kansas Steer Futurities (seven year summary) - Lambert, C.; Brazle, F.; Corah, L.; Schalles, R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Since the fall of 1976, 370 calves and 330 yearlings have been fed through the Southeast Kansas Steer Futurities. In four of the last seven years, both age categories have shown profits through the feedlot phase, using incoming market values assigned by professional market managers, actual feedlot performance and expenses, and slaughter value based on grade and yield date. Calves have been more profitable than yearlings in each of the seven years.
Keywords: Beef; Steer; Performance; Profit